Management of intermediate high-risk pulmonary embolism: a single-center retrospective study - Alabi, Fortune O.; Ghaneie, Ashkan; Koury, Ibrahim; Alkhateeb, Hadaya A.; Liu, Jieying; Guo, Mengni; Fawwaz, Baha Aldeen B.; Cordero, Arelis; Umeh, Fred (Frontiers in Cardiovascular Medicine, 2025)
IntroductionApproximately 25% of PE cases are intermediate-risk, with mortality rates between 5% and 25%. Management strategies for intermediate-risk PE remain inconsistent. This study compares clinical outcomes of intermediate high-risk PE patients receiving anticoagulation therapy alone (ACT) vs. those receiving systemic reperfusion therapy (RT) plus anticoagulation.MethodsThis retrospective study at AdventHealth hospitals in Central Florida included adult PE patients with right ventricular strain diagnosed from January 1, 2019, to December 31, 2020. Exclusions were patients needing vasopressors or invasive ventilatory support at admission and those treated primarily with mechanical thrombectomy or catheter-directed thrombolytic therapy. Patients were divided into two groups: standard ACT and systemic RT plus ACT. Demographics, comorbidities, lab values, treatments, and outcomes were collected and compared.ResultsOf 641 patients, 461 met inclusion criteria, with a median age of 65 and median BMI of 31.2. The cohort included 216 high-risk intermediate PE patients, with 52 patients receiving the thrombolytic therapy and 164 receiving the anticoagulation therapy. There was no significant difference in in-hospital (p = 0.450) or 30-day mortality rates (p = 0.591) between the two treatment groups. Secondary outcomes, including major bleeding (p = 0.569), use of vasopressors (p = 0.969), mechanical ventilation (p = 0.804), CPR (p = 0.450), or transfusion, also showed no significant difference. Notably, 23.2% of patients in the anticoagulation-only group required secondary thrombolytic therapy within 24 hours. Patients receiving systemic RT were younger (p = 0.017) and had a higher BMI (p = 0.012).DiscussionThis study supports guidelines advising against routine use of RT for intermediate high-risk PE unless as rescue therapy. No mortality rate reduction or secondary outcome benefits were observed, highlighting the need for consistent management protocols and further research on therapeutic approaches for intermediate high-risk PE.